An Insight into the Biology of the Rare and Peculiar Moss Pterygoneurum sibiricum (Pottiaceae): A Conservation Physiology Approach - Bojana Z. Jadranin; Marija V. Ćosić; Djordje P. Božović; Milorad M. Vujičić; Michael S. Ignatov; Elena A. Ignatova; Aneta D. Sabovljević; Marko S. Sabovljević (Plants, 2023)
The biological features of the recently described peculiar and rare pottioid moss species Pterygoneurum sibiricum have been studied. A conservation physiology approach through in vitro axenic establishment and laboratory-controlled tests was applied to learn more about its development, physiology, and ecology. Additionally, ex situ collection for this species was established, and a micropropagation methodology was developed. The results obtained clearly document its reaction to salt stress in contrast to its sibling bryo-halophyte species P. kozlovii. The reaction to exogenously applied plant growth regulators, auxin and cytokinin, can be used in the different moss propagation phases of this species or for target structure production and development. Inference to the poorly known ecology of this species should also help in recent species records, and thus improve knowledge about its distribution and conservation.